2022
DOI: 10.3390/nano12030474
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Roles of Metal Loading on CO2 Photocatalytic Reduction Behaviors of TiO2

Abstract: The photocatalytic reduction of carbon dioxide (CO2) into value-added chemicals is considered to be a green and sustainable technology, and has recently gained considerable research interest. In this work, titanium dioxide (TiO2) supported Pt, Pd, Ni, and Cu catalysts were synthesized by photodeposition. The formation of various metal species on an anatase TiO2 surface, after ultraviolet (UV) light irradiation, was investigated insightfully by the X-ray absorption near edge structure (XANES) technique. CO2 red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 88 publications
2
9
0
Order By: Relevance
“…S5†), it can be concluded that compared to the support, the 1Pd/ catalyst binds CO 2 more strongly, since all the peaks are shifted to higher temperatures. Such a phenomenon has already been reported for Pd/TiO 2 45 and Pt/TiO 2 catalysts, 46,47 suggesting an increased surface basicity upon noble metal addition. The peak at around 100 °C has been attributed to the desorption signal of CO 2 weakly interacting with the TiO 2 support (weak surface basic sites).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…S5†), it can be concluded that compared to the support, the 1Pd/ catalyst binds CO 2 more strongly, since all the peaks are shifted to higher temperatures. Such a phenomenon has already been reported for Pd/TiO 2 45 and Pt/TiO 2 catalysts, 46,47 suggesting an increased surface basicity upon noble metal addition. The peak at around 100 °C has been attributed to the desorption signal of CO 2 weakly interacting with the TiO 2 support (weak surface basic sites).…”
Section: Resultssupporting
confidence: 69%
“…S5 †), it can be concluded that compared to the TiO 2 * support, the 1Pd/TiO 2 * catalyst binds CO 2 more strongly, since all the peaks are shifted to higher temperatures. Such a phenomenon has already been reported for Pd/TiO 2 45 and Pt/TiO 2 catalysts, 46,47 suggesting an 46 This might be due to a decrease of adsorption sites (O v and surface Na) after Pd deposition. It is nevertheless important to note that the presence of Pd during catalysis may lead to the generation of O v and Ti 3+ sites on the support, which are favorable for strong or medium adsorption of CO 2 .…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…It is well known that upon UV light irradiation, for example UV components from direct solar light, only the semiconductor, i.e., TiO 2 , is excited. In this circumstance, to improve the photocatalytic potential of a product with TiO 2 , doping the photocatalytic material with metal nanoparticles, allows these latter to act as a kind of sink for electrons induced by light photons, via the Schottky barrier, a condition that prolongs the lifespan of these electrons, by reducing the recombination rate 52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…Photocatalytic CO 2 reduction has been extensively studied with a range of materials, including semiconductor quantum dots, , metal-oxide semiconductors, graphene and its derivatives, , graphitic carbon nitride ( g -C 3 N 4 ), , framework materials, , and transition metal complexes , as well as their composites. , Among these materials, semiconducting CdS quantum dots (QDs) have emerged as highly effective catalysts for light-driven CO 2 reduction due to their unique properties, which allow simple modulation of energy band gaps by varying dot sizes, compositions, and capping agents. This characteristic maximizes solar light absorption and electron transfer. , In addition, intrinsic quantum confinement effects endow CdS QDs with tunable redox potential and photoreduction selectivity .…”
Section: Introductionmentioning
confidence: 99%